Penerapan Penjadwalan Program Kerja Indonesian Future Leaders Chapter Malang Menggunakan Algoritme Genetika - Rafely Chandra Rizkilillah; Budi Darma Setiawan; Marji Marji (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Indonesian Future Leaders is a youth-led Non-Governmental Organization concerning on social activies education and youth empowerment. Indonesian Future Leaders is moved by implementing a variety of work programs that have been created and designed by Indonesian Future Leaders itself. Indonesian Future Leaders work programs are required to be done in a structured way. The programs that are being implemented by Indonesian Future Leaders takes about one year. The problems that Indonesian Future Leaders has is they didn't have structured work program schedules from the start of the beginning starting period. The data that is used by this research are all the work programs of Indonesian Future Leaders. Afterwards, the data will be proceeds with Genethics Algorithm with various of steps, such as cromosom representation, crossover, mutation, evaluation, and selection. The results of the schedule from Genetic Algorithm examination is the best fitness schedule has value of 0,001524 , which has 180 generation combination, 240 populations, and value of 0,7 cr and 0,3 mr.